1985
DOI: 10.1051/rnd:19850807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protozoa on rumen protein degradation in sheep

Abstract: Summary.1. We have studied the contribution of ciliate protozoa to the degradation of dietary protein, utilizing 5 defaunated and 6 faunated sheep. Rumen samples from these animals were used as inocula for in vitro determination of the degradability of different protein sources : lupine grain, peanut and soybean cake, and fish meal. We also applied the in sacco method to measure the digestibility of soybean proteins. Two pore sizes (50 and 100 pm) were used in the in sacco study. The nitrogen degradation curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“….These values are similar to those calculated theoretically18) .While35%of degraded cellulose carbon was converted into cell materials in the absence of protozoa .These results suggest that microbial synthesis would be more efficient in the defaunated sheep rumen and agree with those obtained in vivo experiments2, 19) .As most protozoa show some preferences for species in the engulfment of bacteria20),modification of bacterial flora in addition to the reduction of population size would be expected .Present results which showed a marked decrease in gram negative cocci ,rods and selenomonads-like large curved rods after inoculation of protozoa can be explained by a selective predation and a nutritional competition between protozoa and bacteria .Changes in Entodinium fauna composition after inoculation of D .affine and P.multivesiculatum is interesting; latter is considered as a carnivorous species which engulfs other protozoa such as Epidinium21 multivesiculatum on the one hand and the importance of substrate particle size in this type of assay on the other hand.…”
Section: Discussionsupporting
confidence: 82%
“….These values are similar to those calculated theoretically18) .While35%of degraded cellulose carbon was converted into cell materials in the absence of protozoa .These results suggest that microbial synthesis would be more efficient in the defaunated sheep rumen and agree with those obtained in vivo experiments2, 19) .As most protozoa show some preferences for species in the engulfment of bacteria20),modification of bacterial flora in addition to the reduction of population size would be expected .Present results which showed a marked decrease in gram negative cocci ,rods and selenomonads-like large curved rods after inoculation of protozoa can be explained by a selective predation and a nutritional competition between protozoa and bacteria .Changes in Entodinium fauna composition after inoculation of D .affine and P.multivesiculatum is interesting; latter is considered as a carnivorous species which engulfs other protozoa such as Epidinium21 multivesiculatum on the one hand and the importance of substrate particle size in this type of assay on the other hand.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the increase in N disappearance from the concentrate corresponded to an increase in NH 3 -N. High ruminal NH 3 -N concentration has been associated with large numbers of protozoa in rumen contents (Veira et al, 1983; Towne et al, 1988), presumably a reflection of the predatory activity of these eukaryotes against bacteria (Belanche et al, 2011, 2012) and their ability to degrade feed protein (Ushida et al, 1986). Previous studies demonstrated greater feed protein degradation of diets with low protein solubility in faunated ruminants compared to protozoa-free ruminants (Ushida and Jouany, 1985, 1986; Ushida et al, 1986). The present study is in agreement with these findings, as the linear increase in total and concentrate N disappearance and daily NH 3 -N production observed with increasing proportions of bison inoculum is consistent with the increase in total protozoa numbers.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies with faunated and protozoa-free ruminants have documented that the role of protozoa in feed protein degradation becomes more important as diet protein solubility decreases 37, 38 . The increase in diet N digestibility as a result of the bison rumen content transfer is consistent with the increase in total protozoa counts.…”
Section: Discussionmentioning
confidence: 99%